Comparison of the effects of different concentrations of sodium carboxymethylcellulose on prevention of intraabdominal adhesions in rats - Durmus, A. S.; Han, M. C. (Ecole Nationale Veterinaire Toulouse, 2006)
This experiment was conducted to compare the effects of different concentrations of sodium carboxymethylcellulose (SCMC) on prevention of experimentally induced intraabdominal adhesions in rats. Sixty male Wistar albino rats were divided into four equal groups. An adhesion model was constituted in the caecum and most caudal segment of the ileum of all rats. The lesion areas of rats from the first, second and third groups were coated with a 1 %, 2 % and 3 % SCMC solutions, respectively. Additionally, 7 ml/kg of body weight of a 1 %, 2 % and 3 % SCMC solution were instilled in the peritoneal cavity of animals of the first, second and third group respectively. For the fourth group (control group), a 0.9 % saline solution was used to coat the lesion area and 7 ml/kg of body weight of the same solution was instilled in the peritoneal cavity of each animal. Fourteen days later the rats were sacrificed and the adhesions were graded according to degree of severity. In conclusion, intra-peritoneal administration of SCMC is significantly effective in preventing intraabdominal adhesion formation in rat model.
Keywords: sodium carboxymethylcellulose (SCMC); intraabdominal adhesions; rat